SPAWNING AND EARLY DEVELOPMENT OF THE MARINE PRAWN PARAPENAEOPSIS STYLIFERA (H. MILNE EDWARDS) IN THE LABORATORY - Thomas, M M; George, K V; Kathirvel, M (Indian Journal of Fisheries, 2011)
SPAWNING AND EARLY DEVELOPMENT OF THE MARINE PRAWN PARAPENAEOPSIS STYLIFERA (H. MILNE EDWARDS) IN THE LABORATORY